2001
DOI: 10.1074/jbc.m004750200
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity within Animal Thioredoxin Reductases

Abstract: Animal thioredoxin reductases (TRs) are selenocysteine-containing flavoenzymes that utilize NADPH for reduction of thioredoxins and other protein and nonprotein substrates. Three types of mammalian TRs are known, with TR1 being a cytosolic enzyme, and TR3, a mitochondrial enzyme. Previously characterized TR1 and TR3 occurred as homodimers of 55-57-kDa subunits. We report here that TR1 isolated from mouse liver, mouse liver tumor, and a human T-cell line exhibited extensive heterogeneity as detected by electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 36 publications
(67 reference statements)
1
36
0
Order By: Relevance
“…This band appears to correspond to a potential polypeptide product generated by alternative splicing of TrxR2 transcripts, a phenomenon that was previously reported by Sun et al (57).…”
Section: Mitochondrial Antioxidant Enzymes In Trxr2-overexpress-supporting
confidence: 49%
See 2 more Smart Citations
“…This band appears to correspond to a potential polypeptide product generated by alternative splicing of TrxR2 transcripts, a phenomenon that was previously reported by Sun et al (57).…”
Section: Mitochondrial Antioxidant Enzymes In Trxr2-overexpress-supporting
confidence: 49%
“…This result suggests that the partial localization of TrxR2 in the cytosol is not restricted to mouse tissues nor related to a neuronal or tumor origin, because HeLa originated from a uterine human cancer and COS-7 is an immortalized African green monkey kidney cell line. Most interesting, the sites of junction of the MTS coding exon of the mammalian TrxR2 gene correspond to those found in the Drosophila thioredoxin reductase TR gene, which produces both a cytoplasmic and a mitochondrial TR isoform in the fly (57,84). The similar production of mitochondrial and cytosolic TrxR2 isoforms in mammalian cells suggests a conserved mode of TrxR2 expression during evolution (84).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, a tagged form of TrxR3 was found in mitochondria (19). A more recent report demonstrated that in addition to the products of the three different TrxR genes, both TrxR1 and TrxR3 exhibit extensive heterogeneity due to differential transcript splicing (18). Comparison between mouse, rat, and human revealed that the multiple isoforms are conserved in mammals (18).…”
mentioning
confidence: 99%
“…These additional motifs include an N-terminal disulfide active center, NADPH-and FAD-binding domains, and a dimer interface sequence necessary for homodimerization of the enzymes (4,16,17). Furthermore, sequence homology analyses revealed that TrxR1 and TrxR2 are closely related, whereas TrxR3 is the evolutionarily more distant enzyme but which still exhibits more than 50% overall sequence identity (18).…”
mentioning
confidence: 99%